Measurement of the relative branching ratio of Bs0→J/ψf 0(980) to Bs0→J/ψ - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Askew, A.; et al. (American Physical Society (APS), 2012)
We present a measurement of the relative branching fraction, R f0, of Bs0→J/ψf 0(980), with f 0(980) →π +π -, to the process Bs0→J/ψ, with →K +K -. The J/ψf 0(980) final state corresponds to a CP-odd eigenstate of Bs0 that could be of interest in future studies of CP violation. Using 8fb -1 of data recorded with the D0 detector at the Fermilab Tevatron Collider, we find R f0=0. 275±0.041(stat)±0.061(syst). © 2012 American Physical Society.